The conundrum in endoscopic management of duodenal polyps: a tertiary cancer center experience. (3rd June 2022) - Lee, Jeffrey H.; Yu, Abraham C.; Ali, Faisal S.; Ahmed, Osman; Lynch, Patrick; Ge, Phillip; Coronel, Emmanuel; Kim, Michael; Coronel, Martin; Folloder, Justin; Katz, Matthew H. G.
ABSTRACT: Background: Endoscopic mucosal resection of duodenal polyps (EMR) is a challenging intervention. The aim of this study was to review the patient characteristics, techniques, procedure outcomes, adverse events, and recurrence of duodenal polyps. Research Design and Methods: Patients were included if they had pathologically confirmed non-ampullary duodenal polyps and had received EMR with at least one follow-up EGD for surveillance. Descriptive statistics were employed to report the findings. Results: A total of 65 patients underwent a total of 90 EMRs for duodenal polyps. The mean age was 65.4 years, and 29 of the patients were female. Complete resection of the visible mass was achieved in 96.9% of cases. Endoscopic hemostasis was required in 18.5% of patients. Delayed bleeding occurred in 9%, and delayed perforations requiring surgical intervention occurred in 2.2% of patients with no mortality. Surgery after EMR was needed in 12.7% of cases. Eleven (16.9%) patients had recurrent duodenal adenoma on follow-up EGD. Conclusion: Duodenal polyps can be safely resected and have a notable recurrence rate. This is particularly true for adenomas, warranting post-resection endoscopic surveillance. The appropriate interval for post-resection surveillance of duodenal adenomas should be a focus of future study.